2022
DOI: 10.1007/s00445-022-01588-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-rock oxygen isotope ratios as a proxy for the strength and stiffness of hydrothermally altered volcanic rocks

Abstract: Hydrothermal alteration is considered to increase the likelihood of dome or flank collapse by compromising stability. Understanding how such alteration influences rock properties, and providing independent metrics for alteration that can be used to estimate these parameters, is therefore important to better assess volcanic hazards and mitigate risk. We explore the possibility of using whole-rock δ 18 O and δD values and water contents, metrics that can potentially track alteration, to estimate the strength (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…In total, 19 rock blocks were collected from different locations around the volcano (sampling locations are shown in Figure 1). These blocks have been previously used in recent studies focused on the influence of hydrothermal alteration on the compressive and tensile strength (Heap et al, 2021(Heap et al, , 2022b(Heap et al, , 2022c and the thermal properties (Heap et al, 2022a) of volcanic rocks.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 19 rock blocks were collected from different locations around the volcano (sampling locations are shown in Figure 1). These blocks have been previously used in recent studies focused on the influence of hydrothermal alteration on the compressive and tensile strength (Heap et al, 2021(Heap et al, , 2022b(Heap et al, , 2022c and the thermal properties (Heap et al, 2022a) of volcanic rocks.…”
Section: Methodsmentioning
confidence: 99%
“…We measured oxygen isotopic compositions at the University of Cape Town, South Africa, using a Thermo DeltaXP mass spectrometer. We prepared samples for analysis using the methods described in Heap et al (2022). Duplicates of the internal quartz standard MQ were run with unknowns and used to calibrate the raw data to the Standard Mean Ocean Water scale, using a δ 18 O value of 10.1 ‰ for MQ (calibrated against the quartz standard NBS-28).…”
Section: Whole-rock Oxygen Isotopesmentioning
confidence: 99%
“…Given the lack of visible alteration on our lava samples, we do not consider these positively enriched δ 18 O values to reflect hydrothermal alteration (c.f. Heap et al, 2022).…”
Section: Mantle-derived Magma Supply To Baganamentioning
confidence: 99%
“…Measuring rocks in-situ additionally bypasses complex sample retrieval issues when assessing the mechanical heterogeneity of a volcano, such as highly altered or fractured material which by their nature are often delicate, friable, and difficult to prepare for laboratory analysis. Recent efforts in this direction have shown that rock physical and mechanical properties can be estimated using the percentage by weight (wt.%) of secondary alteration minerals (Heap et al, 2021b), rapid, non-invasive reflectance spectroscopy (Schaefer et al, 2021), and whole-rock oxygen isotopes (Darmawan et al, 2022;Heap et al, 2022) and cation exchange capacity (Revil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%